SISTEM INFORMASI PENJADWALAN MATA PELAJARAN BERBASIS WEB MENGGUNAKAN ALGORITMA GENETIKA (STUDI KASUS: SMK GLOBAL JATITUJUH) - Hidayatullah, Aldi; Suhendri (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2025)
The rapid development of information technology has transformed modern education, particularly in managing school schedules efficiently. In vocational schools like SMK Global Jatitujuh, scheduling conflicts frequently arise due to limited classroom availability, teacher workload, and the addition of new subjects. These conflicts negatively affect teaching efficiency and student learning outcomes. This study proposes a web-based school timetable system using the Genetic Algorithm, an evolutionary computation method that optimizes scheduling through selection, mutation, and crossover operations. The system processes data on subjects, teachers, classrooms, and time slots to generate conflict-free and optimized timetables. The objectives are to implement a web-based scheduling system that minimizes timetable clashes and enhances the efficiency of educational management. Results indicate that the system effectively reduces scheduling conflicts, accelerates timetable generation, and decreases human errors in manual scheduling. In conclusion, the proposed system significantly improves the management of school schedules at SMK Global Jatitujuh, supports the teaching and learning process, and ensures an optimized allocation of educational resources. This approach demonstrates the potential of Genetic Algorithm-based web systems in modern educational scheduling solutions.